The impact of the COVID-19 pandemic on trends in the European banking sector - Miković Nina (Trendovi u Poslovanju)
This article gives a summary of key developments in the European banking industry before and during the global financial crisis, with a focus on trends following the COVID-19 pandemic outbreak. The purpose is to provide an overview with conclusions on the European banking sector's actual and upcoming trends following the COVID-19 pandemic, based on scientific research and reports from selected international financial institutions. The crisis brought on by the COVID-19 pandemic has accelerated the global consolidation process and the advancement of financial technologies, particularly in European banks. In light of the financial crisis' uncertainty and the widespread use of "lockdown" measures, banks in Europe launched a race to digitalize business activities. Banks will also increasingly utilize mergers and acquisitions as a strategy for business model change as competition heats up in the market. However, European banking is undergoing a transformation driven mostly by technological advances. This is both for financial reasons and to stay relevant in the highly competitive digital banking landscape. Green finance are also becoming increasingly popular as a means of promoting environmental sustainability.